2022
DOI: 10.3389/fsurg.2022.1001149
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Giant cell-rich osteosarcoma of the cervical spine in the pediatric age. A rare entity to consider

Abstract: BackgroundAlthough osteosarcoma is the most common primary malignant bone tumor in children, its location in the axial skeleton is rare, particularly at the cervical spine. Early diagnosis, together with multidisciplinary management, improves survival rates. Safe resection and stable reconstruction are complicated by the particular anatomy of the cervical spine, which raises the risks.Case PresentationA 12-year-old male patient presented with cervical pain for several months and a recent weight loss of 3 kg. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Literature search revealed 56 cases of GCRO published between 1986 and 2022 in a total of 34 studies, with 36 cases reported from Asia (64%; Table 3). 10–12,18–50 Mean age was 26 years (range, 5–73 years) and 28 were males (50%). Localizations were reported as follows: Femur (38%; n = 21; 10 times distal, 8 times diaphyseal, 2 times proximal, 1 time unspecified), tibia (27%; n = 15; 14 times proximal, 1 time diaphyseal), mandible ( n = 5), vertebrae C6 to T6 ( n = 4), maxilla ( n = 2), proximal fibula ( n = 2), proximal ulna ( n = 2), foot ( n = 2; first metatarsal, medial cuneiform), 11th rib ( n = 1), skull base ( n = 1), and distal radius ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…Literature search revealed 56 cases of GCRO published between 1986 and 2022 in a total of 34 studies, with 36 cases reported from Asia (64%; Table 3). 10–12,18–50 Mean age was 26 years (range, 5–73 years) and 28 were males (50%). Localizations were reported as follows: Femur (38%; n = 21; 10 times distal, 8 times diaphyseal, 2 times proximal, 1 time unspecified), tibia (27%; n = 15; 14 times proximal, 1 time diaphyseal), mandible ( n = 5), vertebrae C6 to T6 ( n = 4), maxilla ( n = 2), proximal fibula ( n = 2), proximal ulna ( n = 2), foot ( n = 2; first metatarsal, medial cuneiform), 11th rib ( n = 1), skull base ( n = 1), and distal radius ( n = 1).…”
Section: Resultsmentioning
confidence: 99%